The STEREO Mission - Russell, C.T.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
The STEREO mission uses twin heliospheric orbiters to track solar disturbances from their initiation to 1 AU. This book documents the mission, its objectives, the spacecraft that execute it and the instruments that provide the measurements, both remote sensing and in situ. This mission promises to unlock many of the mysteries of how the Sun produces what has become to be known as space weather.
Foreword -- The STEREO Mission: An Introduction -- The STEREO Observatory -- STEREO Space Weather and the Space Weather Beacon -- Sun Earth Connection Coronal and Heliospheric Investigation (SECCHI) -- STEREO IMPACT Investigation Goals, Measurements, and Data Products Overview -- The STEREO IMPACT Boom -- The STEREO/IMPACT Magnetic Field Experiment -- The IMPACT Solar Wind Electron Analyzer (SWEA) -- The STEREO IMPACT Suprathermal Electron (STE) Instrument -- The Suprathermal Ion Telescope (SIT) for the IMPACT/SEP Investigation -- The Low-Energy Telescope (LET) and SEP Central Electronics for the STEREO Mission -- The Solar Electron and Proton Telescope for the STEREO Mission -- The High Energy Telescope for STEREO -- The Plasma and Suprathermal Ion Composition (PLASTIC) Investigation on the STEREO Observatories -- S/WAVES: The Radio and Plasma Wave Investigation on the STEREO Mission -- The Electric Antennas for the STEREO/WAVES Experiment -- STEREO/Waves Goniopolarimetry -- Theoretical Modeling for the STEREO Mission -- STEREO Ground Segment, Science Operations, and Data Archive -- The Solar Terrestrial Relations Observatory (STEREO) Education and Outreach (E/PO) Program.
Keywords: Space sciences; Atmospheric sciences; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Atmospheric Sciences